Class-based weighted window for TCP fairness in WLANs - Seyedzadegan, Mojtaba; Othman, Mohamed (INFOREC Publishing House, 2009)
The explosive growth of the Internet has extended to the wireless domain. The number of Internet users and mobile devices with wireless Internet access is continuously increasing. However, the network resource is essentially limited, and fair service is a key issue in bandwidth allocation. In this research, the focus is on the issue of fairness among wireless stations having different number and direction of flows for different required bandwidth to ensure that fair channel is fairly shared between wireless stations in the same class of bandwidth. It is shown that the current WLANs allocate bandwidth unfairly. It is also identified that the cause of this problem of unfairness is the TCP cumulative ACK mechanism combined with the packet dropping mechanism of AP queue and the irregular space for each wireless station in AP queue. The proposed method allocate converged bandwidth by introducing a Class-Based Weighted Window method which adjusts the TCP window size based on the current conditions of the network and according to the network’s requirements. This method works in wireless stations without requiring any modification in MAC. It can guarantee fair service in terms of throughput among wireless users whether they require the same or different bandwidth.